Deconstruction of “The Pilgrim’s Progress” by John Bunyan in Kurt Vonnegut’s “Slaughterhouse-Five, or The Children’s Crusade” - Nataliya Krynytska (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The US national mythology, one of the components of which is the Puritan cultural heritage, has recently increasingly attracted the attention of researchers of contemporary American literature. The attention often focuses on the problem of the consequences (destructive or beneficial) of postmodern deconstruction regarding the fundamental US myths. The article shows that Kurt Vonnegut in his anti-war postmodernist novel Slaughterhouse-Five manages to create a double code that allows to deconstruct John Bunyan’s important allegorical work The Pilgrim’s Progress, which at one time was an effective means of Protestant religious propaganda, and at the same time to urge readers to return to Christian humanism.